2014
DOI: 10.1212/cpj.0000000000000065
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmune encephalitis mimicking Creutzfeldt-Jakob disease

Abstract: We present a patient with rapidly progressive dementia (RPD) clinically suspicious for prion disease who met clinical criteria for probable and proposed MRI criteria for definite sporadic Creutzfeldt-Jakob disease (sCJD) but was found to have autoimmune encephalitis (AE). 1,2Case report A 69-year-old man with a history of smoking and tremor presented with RPD. During the prior 3 weeks, he lost his job and became increasingly confused, with worsening tremor and difficulty ambulating. At admission, he was orient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…In contrast to a previous study with a mean patient age of 69 years and a male to female ratio of 8:7 (Geschwind et al, 2008), our patients were younger (P = 0.01) and maledominated. According to many case studies, men are more susceptible to VGKC autoimmune encephalitis (Rosenfeld et al, 2012;Fermo et al, 2014;Irani et al, 2011). The age difference may be due to racial differences or may reflect an underestimate of morbidities among elderly patients, who have neurodegenerative diseases more frequently than younger patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to a previous study with a mean patient age of 69 years and a male to female ratio of 8:7 (Geschwind et al, 2008), our patients were younger (P = 0.01) and maledominated. According to many case studies, men are more susceptible to VGKC autoimmune encephalitis (Rosenfeld et al, 2012;Fermo et al, 2014;Irani et al, 2011). The age difference may be due to racial differences or may reflect an underestimate of morbidities among elderly patients, who have neurodegenerative diseases more frequently than younger patients.…”
Section: Discussionmentioning
confidence: 99%
“…Heterogeneity in the imaging data of patients with AE is associated with autoantibody type, in which autoantibodies against intracellular antigens are associated with mesiotemporal abnormalities, whereas autoantibodies against surface antigens are more often associated with either normal findings or abnormalities outside the mesiotemporal region (Rosenfeld et al, 2012), as in our patients. Increased uptake in the left posterior cingulate gyrus, posterior frontal cortex, occipital cortex, thalamus, and precuneus in a patient with the neuronal VGKC antibody suggests an autoimmune process (Fermo et al, 2014). PET imaging of LGI-1 encephalitis reveals altered glucose metabolism, which may be partially relevant to disease stage, but there is a lack of large-scale longitudinal PET investigations due to its cost-effectiveness and radiation exposure.…”
Section: Discussionmentioning
confidence: 99%
“… 6 Even brain MRI, in which abnormal hyperintensity on FLAIR and (diffusion-weighted image) DWI in cortical gyri (cortical ribboning), caudate, putamen or thalamus is considered a very accurate method for diagnosing CJD, has been reported to misdiagnose cases of VGKC encephalitis as CJD. 4 , 5 , 20 Despite the limitation of ancillary testing, a recent test called real-time quacking induced conversion (RT-QuIC) is a very promising premortem diagnostic test. 21 …”
Section: Discussionmentioning
confidence: 99%
“…One study showed that a serial MRI scan within the disease course is necessary for reaching the diagnosis of CJD 5 . Cortical DWI hyperintensity with normal ADC mapping has been reported in autoimmune encephalitis(AE), which is a key neuroimaging clue to distinct AE from sCJD 6 . A PET‐CT scan is useful for improving diagnostic accuracy by showing a hypometabolic pattern in CJD patients 7 .…”
Section: Discussionmentioning
confidence: 99%